Studying engineering at university : everything you need to know - Rhoden, Clare, 1955-; Gordon, Christine Tursky (St Leonards, N.S.W. : Allen and Unwin, 2000)
Transfer issues-from school to university. Learning - the best study skills for you. Memory - hard-writing your knowledge. Note-taking - useful hard copy. Organisation - best practice in timelines. Problem-solving - essential engineering brain food. Pracs, sites and labs - be there, do that...
Keywords: Engineering; Study skills; Engineering -- Study and teaching (Higher)